Health Exposure and Ecological Risk Assessment of Cadmium and Lead in Agricultural Soil in Uasin Gishu, Kenya - Sheriff, S. S.; Simiyu, G. M.; Matasyoh, L. (Africa Environmental Review Journal, 2022)
Increased industrialization, agrochemicals, polluted irrigation water and atmospheric deposition are foremost sources of toxic metals accumulation in proximate agricultural soil. In Kenya, prolonged mono-cropping and farm amendments enhance cadmium and lead accretion in the environment. Hence, understanding anthropogenic activities in the study areas is crucial as human exposure to any level of Lead and Cadmium is unsafe. To evaluate potential impacts of these metals, soil samples were randomly collected from farms in the study areas and analyzed for contamination and ecological health risk using standard procedures. The levels of Cd:Pb in the soil were 0.12:24.84, 0.06:16.46, 0.13:33.29, and 0.13:35.89 for Kaprobu, Kosyin, Moiben, Naiberi and Ziwa, respectively. Cadmium and Lead concentrations exceeded World Health Organization allowable limits of 0.003 mg/kg and 0.1 mg/kg in agricultural soil, but were within limits of United States Environmental Protection Agency, 0.48 mg/kg and 200 mg/kg respectively. The computed Hakanson’s potential ecological risk index (Eri) indicates low to moderate risk of Lead. This is possibly due to intense agricultural activities in the areas and atmospheric deposition. It is concluded that excess use of fertilizer and pesticide aggravates toxic metals in agricultural soils. Recommendation is made to lower agrichemical inputs and regularly monitor soil health to reduce human exposure and health risks.